Soy Isoflavone Extract Does Not Increase the Intoxicating Effects of Acute Alcohol Ingestion in Human Volunteers - Martínez-Riera, Roser; Pérez-Mañá, Clara; Papaseit, Esther; Fonseca, Francina; de la Torre, Rafael; Pizarro, Nieves; Torrens, Marta; Farré, Magí (Frontiers in Pharmacology, 2019)
Soy beans contain isoflavones, including daidzein and genistein, with biological activities which have been related to therapeutic effects in reducing osteoporosis, decreasing adverse menopausal manifestations, providing protection from cardiovascular diseases, and reducing hormone-dependent cancers and age-related cognitive-decline. Daidzein has been described as inhibiting the aldehyde-dehydrogenase-2 enzyme (ALDH2), and reported to reduce alcohol use in clinical pilot studies. Our aim was to evaluate the possible interactions between a soy extract product and alcohol in a crossover, single blind, randomized study. Ten healthy male volunteers participated in two experimental sessions: one with a single dose of alcohol (0.5 g/kg, Vodka Absolut, Sweden), and the other, with four capsules of a soy extract product (Super-Absorbable Soy Isoflavones, Life-Extension, US) and two hours later the same dose of alcohol. Results showed no differences in vital signs except a significant slight higher reduction of diastolic blood pressure at 2, 3, 4, and 8 h after administration with alcohol alone in comparison with soy extract + alcohol. Ethanol-induced subjective and adverse effects were similar for both conditions except for headache (higher at 8h after alcohol alone). Our results demonstrate that a single dose of a soy isoflavone extract did not influence alcohol pharmacokinetics and effects, and did not induce any disulfiram-reaction symptoms. Soy extract and alcohol did not interact and can be administered safely.